2018
DOI: 10.1038/s41598-018-26079-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of Axc, a novel beta-lactamase with carbapenemase activity in a meropenem-resistant clinical isolate of Achromobacter xylosoxidans

Abstract: The development of antibiotic resistance during treatment is a threat to patients and their environment. Insight in the mechanisms of resistance development is important for appropriate therapy and infection control. Here, we describe how through the application of mass spectrometry-based proteomics, a novel beta-lactamase Axc was identified as an indicator of acquired carbapenem resistance in a clinical isolate of Achromobacter xylosoxidans. Comparative proteomic analysis of consecutively collected susceptibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
10
0
2
Order By: Relevance
“…Some in vitro studies demonstrated that mutations in transcription regulators of unnamed ␤-lactamases, or increased expression of a putative ␤-lactamase gene (i.e., bla AXC ), may contribute to carbapenem resistance in Achromobacter spp. (43,57,58). Comparative genomic analysis of carbapenem-susceptible and -resistant strains is essential to elucidate the genetic mechanisms behind carbapenem resistance of genus Achromobacter.…”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…Some in vitro studies demonstrated that mutations in transcription regulators of unnamed ␤-lactamases, or increased expression of a putative ␤-lactamase gene (i.e., bla AXC ), may contribute to carbapenem resistance in Achromobacter spp. (43,57,58). Comparative genomic analysis of carbapenem-susceptible and -resistant strains is essential to elucidate the genetic mechanisms behind carbapenem resistance of genus Achromobacter.…”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…A clinical isolate of A. xylosoxidans resistant to meropenem with increased levels of a novel betalactamase with carpabanemase activity, Axc, and an amino acid substitution at position 29 of the axyZ gene (V29G) suggests that axc expression is regulated by AxyZ [44]. The putative TetR family transcriptional regulator, encoded by the axyZ gene, functions as a negative regulator of the AxyXY-OprZ efflux pump.…”
Section: Resultsmentioning
confidence: 99%
“…В дополнение к существующим конститутивным бета лактамазам, ахромобактерии могут приобретать гены карбапенемаз bla NDM1 [55], bla VIM1 и bla VIM2 [56,57], bla IMP19 [58], bla IMP1 [59], axc [60]. У A. xylosoxidans были найдены обеспечивающие устойчивость к сульфанила мидам/триметоприму плазмидные гены dfrA1 и dfrA16 (кодируют триметоприморезистентную дигидрофолатре дуктазу) и гены sul1 (кодируют сульфаниламидрезистент ную дигидроптероатсинтазу) [34,61].…”
Section: устойчивость к антибиотикамunclassified